Targeting of fibroblast activation protein in rheumatoid arthritis patients: imaging and ex vivo photodynamic therapy. (27th August 2021) - Dorst, Daphne N; Rijpkema, Mark; Buitinga, Mijke; Walgreen, Birgitte; Helsen, Monique M A; Brennan, Evan; Klein, Christian; Laverman, Peter; Ramming, Andreas; Schmidkonz, Christian; Kuwert, Torsten; Schett, Georg; et al.
Abstract: Objective: Activated synovial fibroblasts are key effector cells in RA. Selectively depleting these based upon their expression of fibroblast activation protein (FAP) is an attractive therapeutic approach. Here we introduce FAP imaging of inflamed joints using 68 Ga-FAPI-04 in a RA patient, and aim to assess feasibility of anti-FAP targeted photodynamic therapy (FAP-tPDT) ex vivo using 28H1-IRDye700DX on RA synovial explants. Methods: Remnant synovial tissue from RA patients was processed into 6 mm biopsies and, from several patients, into primary fibroblast cell cultures. Both were treated using FAP-tPDT. Cell viability was measured in fibroblast cultures and biopsies were evaluated for histological markers of cell damage. Selectivity of the effect of FAP-tPDT was assessed using flow cytometry on primary fibroblasts and co-cultured macrophages. Additionally, one RA patient intravenously received 68 Ga-FAPI-04 and was scanned using PET/CT imaging. Results: In the RA patient, FAPI-04 PET imaging showed high accumulation of the tracer in arthritic joints with very low background signal. In vitro, FAP-tPDT induced cell death in primary RA synovial fibroblasts in a light dose-dependent manner. An upregulation of cell damage markers was observed in the synovial biopsies after FAP-tPDT. No significant effects of FAP-tPDT were noted on macrophages after FAP-tPDT of neighbouring fibroblasts. Conclusion: In this study the feasibility of selective FAP-tPDT in synovium of rheumatoid arthritis patients ex vivo is demonstrated. Furthermore, this study provides the first indication that FAP-targeted PET/CT can be used to image arthritic joints, an important step towards application of FAP-tPDT as a targeted locoregional therapy for RA.